Folic Acid-Functionalized Black Phosphorus Quantum Dots for Targeted Chemo-Photothermal Combination Cancer Therapy - Luo, Miaomiao (Pharmaceutics, 2019)
Due to the inherent limitations, single chemo or photothermal therapies (PTT) are always inefficient. The combination of chemotherapy and PTT for the treatment of cancers has attracted a great interest during the past few years. As a photothermal agent, black phosphorus quantum dots (BPQDs) possess an excellent extinction coefficient, high photothermal conversion efficacy, and good biocompatibility. Herein, we developed a photo- and pH-sensitive nanoparticle based on BPQDs for targeted chemo-photothermal therapy. Doxorubicin (DOX) was employed as a model drug. This nanosystem displayed outstanding photothermal performance both in vitro and in vivo. Folic acid conjugation onto the surface endowed this system an excellent tumor-targeting effect, which was demonstrated by the cellular targeting assay. The BPQDs-based drug delivery system exhibited pH- and photo-responsive release properties, which could reduce the potential damage to normal cells. The in vitro cell viability study showed a synergistic effect in suppressing cancer cell proliferation. Therefore, this BPQDs-based drug delivery system has substantial potential for future clinical applications.